2021
DOI: 10.1146/annurev-pharmtox-030220-121042
|View full text |Cite
|
Sign up to set email alerts
|

Use of DREADD Technology to Identify Novel Targets for Antidiabetic Drugs

Abstract: G protein–coupled receptors (GPCRs) form a superfamily of plasma membrane receptors that couple to four major families of heterotrimeric G proteins, Gs, Gi, Gq, and G12. GPCRs represent excellent targets for drug therapy. Since the individual GPCRs are expressed by many different cell types, the in vivo metabolic roles of a specific GPCR expressed by a distinct cell type are not well understood. The development of designer GPCRs known as DREADDs (designer receptors exclusively activated by a designer drug) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 112 publications
0
24
0
Order By: Relevance
“…Originally, beta-arrestins were identified as regulators of GPCR internalization and desensitization [22]; however, more recent studies have shown that beta-arrestins can also act as signaling molecules on their own, mediating G protein-independent signaling [23][24][25][26][27][28][29][30]. GPCRs modulate a very large number of metabolic functions including glucose production, glucose uptake, insulin action, insulin secretion, and differentiation and expansion of various cell types [5,[31][32][33][34][35][36][37]. Thus, it is not surprising that GPCRs have emerged as prime drug targets for the treatment of metabolic diseases such as obesity and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, beta-arrestins were identified as regulators of GPCR internalization and desensitization [22]; however, more recent studies have shown that beta-arrestins can also act as signaling molecules on their own, mediating G protein-independent signaling [23][24][25][26][27][28][29][30]. GPCRs modulate a very large number of metabolic functions including glucose production, glucose uptake, insulin action, insulin secretion, and differentiation and expansion of various cell types [5,[31][32][33][34][35][36][37]. Thus, it is not surprising that GPCRs have emerged as prime drug targets for the treatment of metabolic diseases such as obesity and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, CNO treatment of the various DREADD mutant mice resulted in robust metabolic phenotypes. In many cases, the observed phenotypic changes were more pronounced when mice were maintained on a high-fat (obesogenic) diet which causes impaired glucose tolerance and insulin sensitivity, two hallmarks of type 2 diabetes (T2D) (8,12). To demonstrate that DREADD-mediated responses do not diminish over time, several studies also examined the metabolic effects of chronic CNO treatment [e.g (13)(14)(15)].…”
mentioning
confidence: 99%
“…Activated G protein α-subunits stimulate or inhibit distinct intracellular effector enzymes or ion channels. This figure represents a modified version of Figure 1 published in ( 8 ). Epac, exchange protein activated by cAMP; GIRK, G-protein-regulated inward-rectifier potassium channel; LARG, Leukemia-Associated RhoGEF; PLCβ, phospholipase Cβ; PKA, protein kinase A; PKC, protein kinase C; RhoGEF, Rho guanine nucleotide exchange factor; ROCK, Rho-associated coiled-coil-containing protein kinase; VDCC, voltage-dependent Ca 2+- channel.…”
mentioning
confidence: 99%
See 2 more Smart Citations